Nutrient Analysis of Compost from Different Raw Materials with the Addition of Diaper Waste Hydrogel - Rasyidah, Rasyidah; Selvia, Irda Nila (El-Hayah:Jurnal Biologi, 2025)
Disposable baby diapers are a type of product that is now widely used by the public, but produces large amounts of waste which poses environmental challenges. The way to process this waste is by recycling into additional solid organic fertilizer materials. This study aims to determine the increase in nutrients due to the addition of diaper waste hydrogel to compost products with different raw materials. The parameters observed to measure the quality of the compost are water content, pH, C/N ratio, C-Organic, N, P, K, Ca, Mg, Cu, Zn, and Mn. The study was conducted with different raw materials (sawdust, cow manure and their combination), with and without the addition of diaper waste hydrogel. The results showed that treatments with added diaper waste hydrogel (P1H, P2H, and P3H) had higher macronutrient and micronutrient levels than treatments without (P1, P2, and P3). Especially, P2H treatment had better suitability and nutrient increase compared to other treatments based on SNI 19-7030-2004.